Value Network, Industry Experience, and Innovation on the Performance of Indonesian Start-Up Companies: A Quantitative Analysis - W`, AG Eka Wenats (Sinergi International Journal of Economics, 2024)
Value networks, industry experience, and innovation are some of the elements that impact the performance of start-up enterprises in Indonesia. Using a survey of 200 start-up founders, executives, and stakeholders, this quantitative study seeks to investigate the connections between these variables and start-up performance with SEM-PLS version 4. The results show a strong positive correlation between start-up performance, industry experience, value network, and innovation. In particular, start-ups with broad and varied networks, seasoned business owners, and an innovative culture typically see increases in revenue growth, market share, profitability, and customer satisfaction. The findings highlight how crucial it is to support innovation-driven projects, cultivate strategic alliances, and invest in human capital to increase start-up success in Indonesia. These conclusions have ramifications for business owners, financiers, decision-makers, and professionals in the field who aim to steer clear of the unstable terrain of the Indonesian startup scene and stimulate economic expansion via innovation and entrepreneurship. The real implications of this study emphasize the need for targeted policy measures and strategic investments that foster a conducive environment for innovation, enhance networking opportunities, and leverage industry expertise. These efforts can significantly contribute to the robustness and competitiveness of Indonesian start-ups, driving sustainable economic growth and development.